THE ROLE OF CMV INFECTION IN FORMATION OF PERINATAL PATHOLOGY - L. B. Kisteneva (LLC "Diagnostics and Vaccines", 2015)
This article covers the issues of pathogenesis, diagnostics, clinical manifestations and treatment of CMV infections at perinatal infection